Inflammation and Corticospinal Functioning in Multiple Sclerosis: A TMS Perspective - Stampanoni Bassi, Mario; Buttari, Fabio; Gilio, Luana; De Paolis, Nicla; Fresegna, Diego; Centonze, Diego; Iezzi, Ennio (Frontiers in Neurology, 2020)
Transcranial magnetic stimulation (TMS) has been employed in multiple sclerosis (MS) to assess the integrity of the corticospinal tract and the corpus callosum and to explore some physiological properties of the motor cortex. Alterations of TMS measures have been evidenced in patients with MS and have been related to different pathophysiological mechanisms, particularly to demyelination. Moreover, TMS studies contributed to define the neurophysiological basis of specific symptoms, as fatigue. Knowledge of MS pathophysiology has been recently enriched by TMS findings showing that inflammation critically influences synaptic functioning in MS. Accordingly, TMS studies have demonstrated that cerebrospinal fluid concentrations of different proinflammatory and anti-inflammatory molecules correlated with measures of corticospinal excitability. These results are in line with preclinical studies in animal models (i.e. experimental autoimmune encephalomyelitis), revealing that different inflammatory molecules alter synaptic transmission, promoting hyperexcitability and neuronal damage. In this perspective article we overview the main TMS studies exploring corticospinal excitability alterations in MS, their pathophysiological correlates and the relationship with MS clinical characteristics and symptoms. Furthermore, we discuss evidence from preclinical and TMS studies indicating inflammatory synaptopathy as a relevant pathophysiological mechanism acting since the early phases of MS.